The GIY‐YIG endonuclease domain of Arabidopsis MutS homolog 1 specifically binds to branched DNA structures. Issue 24 (8th November 2018) - Fukui, Kenji; Harada, Akiko; Wakamatsu, Taisuke; Minobe, Ai; Ohshita, Koki; Ashiuchi, Makoto; Yano, Takato
Abstract : In plant organelle genomes, homeologous recombination between heteroallelic positions of repetitive sequences is increased by dysfunction of the gene encoding MutS homolog 1 (MSH1), a plant organelle‐specific homolog of bacterial mismatch‐binding protein MutS1. The C‐terminal region of plant MSH1 contains the GIY‐YIG endonuclease motif. The biochemical characteristics of plant MSH1 have not been investigated; accordingly, the molecular mechanism by which plant MSH1 suppresses homeologous recombination is unknown. Here, we characterized the recombinant GIY‐YIG domain of Arabidopsis thaliana MSH1, showing that the domain possesses branched DNA‐specific DNA‐binding activity. Interestingly, the domain exhibited no endonuclease activity, suggesting that the mismatch‐binding domain is required for DNA incision. Based on these results, we propose a possible mechanism for MSH1‐dependent suppression of homeologous recombination. Abstract :